Slow light effect in hybrid optomechanical system - Biag, Maryam; Ghaffar, Ammal; Khan, Muhammad Aslam; Khan, Farooq; Niaz, Shanawer (International journal of quantum chemistry, 2022)
We theoretically examined the slow light effect in a one‐sided optomechanical system with a two‐level atom placed inside it. When the cavity without atoms is driven by the input field, an optomechanically induced transparency (OMIT) window appears in the transmission spectrum due to destructive interference. We observed that due to the existence of atoms, the OMIT window shifted to normal‐mode splitting and steeper Fano shapes. Our results exhibit that coupling strength has a very prominent effect on the transmission part. The Larger the coupling strength, the larger will be the effect on the transmission. This leads to rapid positive phase dispersion in the transmitted field, gives rise to the corresponding slow light effect. We observed slow light in an optomechanical cavity system that consists of a two‐level atom (qubit) with one fixed mirror and one moveable mirror driven by strong pump field and weak probe field.